مساهمة في دراسة تنوع األشجار المثمرة المزروعة بولاية الوادي - العياضي, إكرام; حاج سعد, إكرام; معامير, و سام (Université of eloued جامعة الوادي, 2025)
The main objective of our work is to study the diversity of fruit trees planted in the south and Wahat areas in general and in the state of the valley and Ouedi Righ in particular, taking the municipality of Oum thiour as a model, through a field study in which the focus was on a group of characteristics of fruitful trees such as the general shape of trees, characteristics of leaves , flowers, fruits..., in addition to recognizing the degree of similarity between them. Where we found through this study that there is a clear discrepancy in the morphological characteristics of the five types of fruit trees that are abundant in the region, namely: apricot trees, fig trees, orange trees, mulberry trees, pomegranate trees, whether they are within the same species or between species despite their spread in one geographic location, This was confirmed by the specific statistical results of the degree of morphological kinship that we conducted, through which it was found that two samples of trees within the same species are often similar, which means that they inevitably belong to the same family, while the other sample is different and thus follows another family, and therefore all these results refer to That there is a wide biological diversity of fruit trees in the state of Eloued .
التنوع الحيوي وفزيولوجيا النبات
Keywords: تنوع بيولوجي، درجة القرابة، األشجار المثمرة، الواحات ، أم الطيور، وادي ريغ.; biological diversity; degree of kinship; fruit trees; Oum thiour; Ouedi Righ.